An annotated checklist of Brazilian sea spiders (Arthropoda: Pycnogonida) - Lucena, Rudá Amorim; Christoffersen, Martin Lindsey (Zootaxa, 2018)
The Brazilian coast is over 7000 km long. It is comprised of diverse environments such as reef, lagoons and mangroves. These diverse habitats support great biological diversity but, due to the extension of the coast, knowledge of the pycnogonid fauna is poor and fragmented. Records from Brazil began with Krøyer in the 1840s. Collections from Brazilian waters by the "H.M.S. Challenger" and "Vettor Pisani" expeditions were published by Hoek (1881) and Schimkewitsch (1888). For almost 50 years there were no further publications, until Marcus (1940c) published his comprehensive paper on the South American fauna. Publications peaked between the 1940s and 1960s, with papers by Marcus, Sawaya, Mello-Leitão, Corrêa, Du Bois- Reymond Marcus, Hedgpeth and Stock. Approximately 40 papers based on material from Brazilian waters were published at this time, which recorded 65 species for Brazil. The aim of the present work is to provide a checklist of the Brazilian pycnogonids while providing a historical review and a full account of the corresponding literature.